A 2019-20 social accounting matrix for Balochistan, Pakistan - Toori, Shafaq; Akram, Iqra; Qureshi, Tehseen Ahmed; Tauqir, Aisha; Raja, Sehrish; Gill, Sitara; Rana, Abdul Wajid (International Food Policy Research Institute, 2023)
This paper documents the different steps followed to construct Social Accounting Matrix (SAM) for Balochistan for the year 2019-20. More precisely, it describes the estimation methods and the nature of the data used in developing the SAM at the subnational level. The Balochistan SAM includes 13 production activities, 4 factors of production, 4 household groups and rest of the world account, assessing linkages between production, factor income distribution, and households’ incomes and expenditures, and capturing distributional effects. The Balochistan SAM reveals that the shares of services and manufacturing sector remains lower than national average and there is an overwhelming contribution of the livestock and horticulture sector in the subnational economy which has the potential in boosting national livestock and horticulture exports. Further, the consumption pattern in Balochistan supports Engle’s law of consumption showing that with an increase in households’ income, the share of expenditure on food decreases and consumption of non-food items increases. This paper is organized as follows. The first section presents an overview of Balochistan province of Pakistan. The second Section highlights the background of Social Accounting Matrix and its key features. The third section review the literature and various efforts made to develop Pakistan SAM with varying features. The fourth section describes the process and the methodology used to develop SAM. The fifth section presents the structure of Balochistan SAM, accounts, and data sources and elaborates the process and techniques used to balance Balochistan SAM. The sixth section highlights the structure of Balochistan’s economy and an evaluation of value addition. The seventh section underscores the key findings of Balochistan SAM. The final section underlines how the SAM Balochistan can contribute to evidence-based policy making that helps in economic growth and reducing poverty in Balochistan.